Sistem Pendukung Keputusan Dalam Pemberian Reward Bagi Dokter Terbaik Dengan Menggunakan Metode Weighted Product - Afdina Tri Dinanti; Dewi Suranti; Reno Supardi (Jurnal Media Infotama, 2023)
ABSTRACT: This study aims to determine the Decision Support System in giving rewards to the best doctors at Hasanuddin Damrah Hospital. Currently the job evaluation system at Hasanuddin Damrah Manna Hospital is still carried out conventionally and the results of the assessment are subjective. The sample in this study was 8 data doctors where in the selection of the best doctor will be determined based on the assessment criteria used the main indicators of assessment. The assessment criteria used at the Hospital are Discipline, Interpersonal & Communication Skills, Patient Care, Writing and Completeness of Medical Records, Professionalism. Based on the results of this study, the authors designed a Decision Support System to evaluate Doctor's Performance using Visual Basic Net Weighted Product (WP).